Effects of Cold Rolling and Annealing Treatment on Microstructure and Properties of CoFeNiMnV High‐Entropy Alloys. Issue 3 (16th November 2022) - Xin, Heyang; Chen, Xizhang; Wang, Yanhu; Su, Chuanchu; Xin, Dongqun; Xia, Jiayi; Liang, Yu
Abstract : Herein, a combination of cold rolling (CR) and annealing treatment is used to investigate the evolution of the microstructure and mechanical properties of CoFeNiMnV high‐entropy alloys (HEAs) fabricated by powder plasma arc additive manufacturing (PPA‐AM). The deposited CoFeNiMnV HEAs exhibit a face‐centered cubic (FCC) structure with a small amount of σ phase precipitation. After 50% CR, the microstructure of CoFeNiMnV HEAs is severely deformed along the rolling direction, and the grain size is obviously refined. Therefore, the hardness and strength of the alloy are significantly improved. The rolled CoFeNiMnV HEAs are annealed at 500, 700 and 900 °C, for 60 min. The results show that annealing at 500 °C has little effect on the microstructure and dislocation density of the alloy, and the alloy still maintains high strength and hardness. With increasing of annealing temperature to 700 and 900 °C, the dislocation density of the CoFeNiMnV HEAs is significantly reduced. Meanwhile the σ phase is gradually dissolved, and the recrystallized grains and annealing twins are significantly coarsened. The analysis suggests that it decreases the strength of the CoFeNiMnV HEAs, but increases the elongation. CoFeNiMnV HEAs annealed at 700 °C for 60 min after CR exhibit an excellent high strength–toughness combination. Abstract : The face‐centered cubic (FCC) phase CoFeNiMnV high‐entropy alloys (HEAs) with high basic strength are prepared by powder plasma arc additive manufacturing (PPA‐AM). An innovative approach combining PPA‐AM, cold rolling (CR), and annealing is used to study the microstructure evolution and mechanical property differences of deposited, cold rolled, and annealed CoFeNiMnV HEAs. CoFeNiMnV HEAs annealed at 700 °C for 60 min after CR exhibit an excellent high strength–toughness combination.